Current Research on Gender Issues in Advertising - Zotos, Yorgos and Grau, Stacy and Taylor, Charles R. (Taylor & Francis, 2018)
Gender stereotypes are general beliefs about sex-linked traits and roles, psychological characteristics, and behaviors, all of which contribute towards describing women and men. Gender role stereotyping in advertising has been a critical topic since the 1970s, and there is a long-lasting debate between advertisers and sociologists about the role and the social nature of advertising. Although changing role structures in the family and the labor force have brought significant variation in both male and female roles, it has been noted that there is a cultural lag in advertising, where men and women were, for a long period of time, depicted in more traditional roles. -- This book extends the research on gender stereotypes in advertising over the past 20 years, highlighting key themes such as attitude towards sex and nudity in advertising; women in decorative roles; the changing roles of women and men in advertising; and the viewpoints of those advertising professionals who design campaigns. This book was originally published as a special issue of the International Journal of Advertising.
https://katalog.adlr.link/Record/51-9780815380207